The Mathematical Expressions of Quranic Exegeses and the Mathematical Definition of the Quranic Correctness - Tahara, Hiroki (Journal of Islam and Science, 2020)
This study succeeded in giving mathematical expressions to any correct Quranic exegeses and define the Quranic correctness as the unique existence of Tahara I function. In a precise mathematical sense, the expressions and the definition are ill-defined. However, they might have meanings to prove the Quranic correctness.